2022
DOI: 10.1088/1475-7516/2022/09/045
|View full text |Cite
|
Sign up to set email alerts
|

Smooth coarse-graining and colored noise dynamics in stochastic inflation

Abstract: We consider stochastic inflation coarse-grained using a general class of exponential filters. Such a coarse-graining prescription gives rise to inflaton-Langevin equations sourced by colored noise that is correlated in e-fold time. The dynamics are studied first in slow-roll for simple potentials using first-order perturbative, semi-analytical calculations which are later compared to numerical simulations. Subsequent calculations are performed using an exponentially correlated noise which appears as a leading … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…The choice of final boundary conditions in this paper and in [67,78] differs from that of many other studies, which employ the first passage time formalism [41,49,52,57,60,64,73,74,79,[81][82][83][84]. There the stochastic kicks continue all the way to the end of the computation, which terminates when the field first crosses the final hypersurface at φ = φ final .…”
Section: Discussionmentioning
confidence: 99%
“…The choice of final boundary conditions in this paper and in [67,78] differs from that of many other studies, which employ the first passage time formalism [41,49,52,57,60,64,73,74,79,[81][82][83][84]. There the stochastic kicks continue all the way to the end of the computation, which terminates when the field first crosses the final hypersurface at φ = φ final .…”
Section: Discussionmentioning
confidence: 99%
“…The choice of final boundary conditions in this paper and in [67,78] differs from that of many other studies, which employ the first passage time formalism [41,49,52,57,60,64,73,74,79,[81][82][83][84]. There the stochastic kicks continue all the way to the end of the computation, which terminates when the field first crosses the final hypersurface at φ = φ final .…”
Section: Jcap04(2023)042mentioning
confidence: 99%
“…There has been a profusion of work on SI in the recent literature in the context of PBH formation [56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74], and it has been shown that SI generically predicts a (highly non-Gaussian) exponential tail in the PDF [56,59]. However, since PBH formation usually requires slow-roll violation, it is important to develop the SI formalism beyond slow-roll [57,[60][61][62]66].…”
Section: Jcap09(2023)005mentioning
confidence: 99%
“…This assumption has been questioned, especially because the sharp cut-off window function may not lead to well-behaved coarse-grained field correlators in the physical space. See refs [73,88,89]. for more discussion.…”
mentioning
confidence: 99%